Counselling strategies in economic blogs - Suska, Dorota (Papers in Linguistics, 2019)
This article presents a pragmalinguistic description of economic blogs as a representation of contemporary discourse counselling. The analyses focus on a description of the textual activities of the bloggers, which aim to initiate dialogue with the recipient and to shape it according to the planned strategy. The author discusses the titles of blogs as an initial paratext, then distinguishes two types of economic blogs: expert and practical (based on such pragmatic parameters as: relations between sender and recipient, official - unofficiality, advisory procedures).